Assessment of the challenges influencing the adoption of smart building technologies - Baharetha, Saleh; Soliman, Ashraf M.; Hassanain, Mohammad A.; Alshibani, Adel; Ezz, Mohamed Salah (Frontiers in Built Environment, 2024)
Introduction: Over the past few decades, there has been an increasing focus on Smart Building Projects (SBP) and the technologies associated with them. Numerous studies have been conducted globally to define smart building technologies (SBT), identify challenges, and explore areas for improvement. This study aims to examine the concept and terminology of SBT and the expertise and experience of participants in SBP in the Arab Gulf countries, specifically Saudi Arabia. The study also investigates the challenges faced by SBT throughout its life cycle. Methods: To identify and assess the challenges affecting the adoption of smart building technologies. This approach included a literature review, pilot-testing, and a questionnaire survey. The survey targeted a sample of 90 architects/engineers, managers, and contractors. Results: A total of 55 challenges were identified and categorized into four groups, corresponding to the key phases of the project life cycle. These phases include the programming and feasibility analysis phase, design phase, installation and commissioning phase, and operation and maintenance phase. The findings of this research expand the body of knowledge by providing architects/engineers, managers, and contractors in the architecture, engineering, construction, and facility management (AEC/FM) industry with insights into the influential challenges related to the adoption of SBT. In conclusion, this study sheds light on the concept and terminology of smart building technologies and explores the challenges faced by SBT during its life cycle. By identifying and categorizing these challenges, the study provides valuable information to AEC/FM practitioners, enabling them to overcome obstacles and improve the adoption of SBT.